Effect of Matra Basti with Mahanarayana Taila in Sandhigata Vata w.s.r. Osteoarthritis-A Single Case Study. - Farheen, Neha; Nigam, Rachna (International Research Journal of Ayurveda & Yoga, 2023)
Now a days Osteoarthritis (OA) is the most common musculoskeletal abnormality. In Ayurveda the disease Sandhigata Vata resembles with OA, which is described under Vatavyadhi. It is a degenerative joint disease that mostly affects weight-bearing joints, such as the knee joint mostly in Vridhavastha.Ayurvedic approach in management of Sandhigatvata can be the best treatment modality. In panchakarma basti is the best treatment for Vatavyadhi. considering this Matra basti with Mahanarayana taila is selected to access the outcome. A female patient of 65 years old came in opd with complaining of bilateral knee joint pain for 8 years. Difficulty while walking for 2 years. There was a significant joint space reduction with osteophyte in X-ray of bilateral knee joint.In this disease Matra basti with Mahanarayana taila is found to be the best treatment in Sandhigata Vata.